Tools and strategies for scarless allele replacement in Drosophila using CRISPR/Cas9. Issue 1 (2nd January 2017) - Lamb, Abigail M.; Walker, Elizabeth A.; Wittkopp, Patricia J.
ABSTRACT: Genome editing via the CRISPR/Cas9 RNA-guided nuclease system has opened up exciting possibilities for genetic analysis. However, technical challenges associated with homology-directed repair have proven to be roadblocks for producing changes in the absence of unwanted, secondary mutations commonly known as "scars." To address these issues, we developed a 2-stage, marker-assisted strategy to facilitate precise, "scarless" edits in Drosophila with a minimal requirement for molecular screening. Using this method, we modified 2 base pairs in a gene of interest without altering the final sequence of the CRISPR cut sites. We executed this 2-stage allele swap using a novel transformation marker that drives expression in the pupal wings, which can be screened for in the presence of common eye-expressing reporters. The tools we developed can be used to make a single change or a series of allelic substitutions in a region of interest in any D. melanogaster genetic background as well as in other Drosophila species.